Basic Fibroblast Growth Factor Stimulates the Proliferation of Bone Marrow Mesenchymal Stem Cells in Giant Panda (Ailuropoda melanoleuca). - Jun-Jie Wang; Yu-Liang Liu; Yuan-Chao Sun; Wei Ge; Yong-Yong Wang; Paul W Dyce; Rong Hou; Wei Shen (PLoS ONE, 2015)
It has been widely known that the giant panda (Ailuropoda melanoleuca) is one of the most endangered species in the world. An optimized platform for maintaining the proliferation of giant panda mesenchymal stem cells (MSCs) is very necessary for current giant panda protection strategies. Basic fibroblast growth factor (bFGF), a member of the FGF family, is widely considered as a growth factor and differentiation inducer within the stem cell research field. However, the role of bFGF on promoting the proliferation of MSCs derived from giant panda bone marrow (BM) has not been reported. In this study, we aimed to investigate the role of bFGF on the proliferation of BM-MSCs derived from giant panda. MSCs were cultured for cell proliferation analysis at 24, 48 and 72 hrs following the addition of bFGF. With increasing concentrations of bFGF, cell numbers gradually increased. This was further demonstrated by performing 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT) cell proliferation assay, 5-Bromo-2-deoxyUridine (BrdU) labeling and cell cycle testing. Furthermore, the percentage of MSCs that were OCT4 positive increased slightly following treatment with 5 ng/ml bFGF. Moreover, we demonstrated that the extracellular signal-regulated kinase (ERK) signaling pathway may play an important role in the proliferation of panda MSCs stimulated by bFGF. In conclusion, this study suggests that giant panda BM-MSCs have a high proliferative capacity with the addition of 5 ng/ml bFGF in vitro.